2018
DOI: 10.1183/23120541.00162-2017
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and natural history ofPseudomonas aeruginosaairway infections in non-cystic fibrosis bronchiectasis

Abstract: The natural history and epidemiology of Pseudomonas aeruginosa infections in non-cystic fibrosis (non-CF) bronchiectasis is not well understood.As such it was our intention to determine the evolution of airway infection and the transmission potential of P. aeruginosa in patients with non-CF bronchiectasis.A longitudinal cohort study was conducted from 1986–2011 using a biobank of prospectively collected isolates from patients with non-CF bronchiectasis. Patients included were ≥18 years old and had ≥2 positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…Our results found that no major Australian CF shared P. aeruginosa strains were detected in our current cohort. In fact, our study found no evidence of shared P. aeruginosa strain infections, which is in keeping with the published data that shared P. aeruginosa strains are uncommon in patients with bronchiectasis or COPD . The P. aeruginosa strains detected in our study are commonly found in other niches, such as the natural environment and non‐CF infections .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results found that no major Australian CF shared P. aeruginosa strains were detected in our current cohort. In fact, our study found no evidence of shared P. aeruginosa strain infections, which is in keeping with the published data that shared P. aeruginosa strains are uncommon in patients with bronchiectasis or COPD . The P. aeruginosa strains detected in our study are commonly found in other niches, such as the natural environment and non‐CF infections .…”
Section: Discussionsupporting
confidence: 92%
“…The P. aeruginosa strains detected in our study are commonly found in other niches, such as the natural environment and non‐CF infections . Our longitudinal analysis of P. aeruginosa isolates showed that the majority of participants retained the same unique P. aeruginosa strain over time, which is consistent with other recent studies . These results suggest that person‐to‐person transmission of P. aeruginosa is unlikely to occur in patients with bronchiectasis and COPD.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations